The Effect of Social Participation on Elderly Live Satisfaction. (March 2017) - Kusmaedi, N; Sultoni, K; Subarjah, H
Abstract: The purpose of this study was to examine the effect of social participation on elderly life satisfaction in the aging process. This study employs expo-facto research method. The design was one parallel static group post-test design. The independent variable of this study is social participation and the dependent variable is life satisfaction in aging process (healthy aging process). The sample of the study was collected through random sampling that was 69 elderly people who live in Bandung. The result shows that there is a significant difference among the four groups ( P < 0.05). The more the social fields that are followed, the higher the life satisfaction. This indicates that social participation affects the elderly life satisfaction.